Study of the cytotoxic effect of modified titanium compounds in a cellular model of resistance to cisplatin - Mendes, Cristina Isabel Branca (2025)
Cancer is still a major cause of death in developed countries, and the search for better therapies to fight this disease has been increasing. This study focuses on evaluating the effectiveness of two newly developed titanium-based compounds, Myr-Ti and OleTi, against ovarian cancer cells that do not respond to standard cisplatin treatment. We employed a range of methods, including western blot analysis, MTT assays, flow cytometry, and DNA binding tests, to determine which compound more effectively targets cancer cells. The results revealed that both compounds showed significant cytotoxic effects, with Ole-Ti demonstrating superior efficacy in reducing cell viability, particularly in cisplatin-resistant cell lines. These promising findings suggest that Myr-Ti and Ole-Ti could serve as potential alternatives for patients who do not respond to traditional therapies. Further research is needed to explore the mechanisms of action and therapeutic potential of these compounds in the ongoing battle against cancer; - Resumo: Estudo do efeito citotóxico de compostos de titânio modificados num modelo celular de resistência à cisplatina - O cancro continua a ser uma das principais causas de morte em países desenvolvidos, e a procura por terapias mais eficazes para combater essa doença continua a aumentar. Este estudo foca-se em avaliar a eficácia de dois novos compostos à base de titânio, Myr-Ti e Ole-Ti, contra células de cancro do ovário que não respondem ao tratamento padrão com cisplatina. Foram utilizados métodos como ensaios MTT e citometria de fluxo que revelaram que ambos os compostos apresentaram efeitos citotóxicos significativos, com Ole-Ti a demonstrar uma maior eficácia na redução da viabilidade celular, particularmente em linhas celulares resistentes à cisplatina. Estes resultados sugerem que Myr-Ti e Ole-Ti podem ser potenciais alternativas para pacientes que não respondem às terapias tradicionais, sendo necessárias pesquisas adicionais para explorar os mecanismos de ação e o potencial terapêutico desses compostos no tratamento do cancro.